2021
DOI: 10.1051/e3sconf/202130202015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium hydroxide pretreatment on released sugar yields from pomelo peels for biofuel production

Abstract: Most of the agricultural wastes in developing countries are disposed of by on-site combustion leading to unmanaged environmental pollutions. Conversion of agricultural wastes to value-added products, such as bioethanol and biogas, is a promising method to reduce agro-waste after harvesting seasons. In this study, Citrus maxima peels (Pomelo peels) was selected to be converted to reducing sugars, which could be a raw material to produce other value-added products. To promote enzymatic hydrolysis reactions, pome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The Figure showed that for the use of base concentrations 0.2 M and 0.4 M have a tendency to the same result, but different tendencies are shown in the use of 0.1 M. At the usage of a lower concentration of alkaline solvents of 0.1 M, the extended in reaction time from 10 minutes to 25 minutes leads to degradation in the reducing sugar obtained from 0.067% to 0.021% and again rose up on the increase in the 30-minute reaction time to 0.076%. This decrease may be due to the destruction of the internal structure of biomass caused by the long pretreatment time (Chatkaew et al, 2021) . The same trend is shown by the results of research conducted by Mandra Harahap et al (2020).…”
Section: Figure 1 the Effect Of Reaction Time And Concentration Of Ac...mentioning
confidence: 99%
“…The Figure showed that for the use of base concentrations 0.2 M and 0.4 M have a tendency to the same result, but different tendencies are shown in the use of 0.1 M. At the usage of a lower concentration of alkaline solvents of 0.1 M, the extended in reaction time from 10 minutes to 25 minutes leads to degradation in the reducing sugar obtained from 0.067% to 0.021% and again rose up on the increase in the 30-minute reaction time to 0.076%. This decrease may be due to the destruction of the internal structure of biomass caused by the long pretreatment time (Chatkaew et al, 2021) . The same trend is shown by the results of research conducted by Mandra Harahap et al (2020).…”
Section: Figure 1 the Effect Of Reaction Time And Concentration Of Ac...mentioning
confidence: 99%
“…Several studies have suggested that the combination of two or more pretreatment methods can yield greater delignification and higher sugar yields than a single pretreatment method [23][24][25][26]. In this work, the effect of combined alkaline pretreatment and Deep eutectic solvent (DES) pretreatment on enzymatic hydrolysis of yellow thatching grass (Hyparrhenia filipendula) is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of biomass structure has resulted in the application of advanced technology such as a pretreatment process to break down its structure to a simpler form. This step will help in breaking down the polymers into monomers and oligomers that can be taken to the downstream processing steps and finally converted to bioethanol [8]. Among various types of pretreatment methods, including physical, chemical, physicochemical, and biological approaches, chemical pretreatment is extensively employed for biomass utilization.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10]. Among the various types of chemical pretreatment, acid pretreatment, and alkaline pretreatment are commonly used techniques [8,11,12]. Acid pretreatment can be done with both organic and inorganic acids, however, the use of inorganic acid generates more inhibitors and can cause corrosion to the equipment than the organic acids [13] and it has the benefit of environmental protection [14].…”
Section: Introductionmentioning
confidence: 99%